background image

Proof

Recall that

I

RLD

A

=

Base(

A

)

I

A

|

A

up

A

 

. For every

X

,

Y ∈

F

(Base (

A

)) we have:

X

(

FCD

)

I

RLD

A

Y ⇔ X ×

RLD

Y 6≍

I

RLD

A

⇔ ∀

A

up

A

:

X ×

RLD

Y 6≍↑

RLD

(Base(

A

);Base(

A

))

I

A

⇔ ∀

A

up

A

:

X

FCD

(Base(

A

);Base(

A

))

I

A

Y ⇔ ∀

A

up

A

:

X ∩

Y 6≍↑

Base(

A

)

A

⇔ X ∩ Y 6≍ A ⇔ X

I

FCD

A

Y

(used properties of generalized

filter bases).

Proposition 33

(

FCD

)(

A ×

RLD

B

) =

A ×

FCD

B

for every f.o.

A

and

B

.

Proof

X

(

FCD

)(

A ×

RLD

B

)

Y ⇔ ∀

F

up(

RLD

B

) :

X

FCD

(Base(

A

);Base(

B

))

F

Y

(for every

X

,

Y ∈

F

).

Evidently

F

up(

A ×

RLD

B

) :

X

FCD

(Base(

A

);Base(

B

))

F

Y ⇒

A

up

A

, B

up

B

:

X

FCD

(Base(

A

);Base(

B

))

(

A

×

B

)

Y

.

Let

A

up

A

, B

up

B

:

X

FCD

(Base(

A

);Base(

B

))

(

A

×

B

)

Y

. Then if

F

up(

A ×

RLD

B

), there are

A

up

A

,

B

up

B

such that

F

A

×

B

. So

X

FCD

(Base(

A

);Base(

B

))

F

Y

.

We proved

F

up(

A ×

RLD

B

) :

X

FCD

(Base(

A

);Base(

B

))

F

Y ⇔ ∀

A

up

A

, B

up

B

:

X

FCD

(Base(

A

);Base(

B

))

(

A

×

B

)

Y

.

Further

A

up

A

, B

up

B

:

X

FCD

(Base(

A

);Base(

B

))

(

A

×

B

)

Y ⇔ ∀

A

up

A

, B

up

B

: (

X 6≍↑

Base(

A

)

A

∧ Y 6≍↑

Base(

B

)

B

)

⇔ X 6≍ A ∧ Y 6≍ B ⇔

X

A ×

FCD

B

Y

.

Thus

X

(

FCD

)(

A ×

RLD

B

)

Y ⇔ X

A ×

FCD

B

Y

.

Proposition 34

dom(

FCD

)

f

= dom

f

and

im(

FCD

)

f

= im

f

for every reloid

f

.

Proof

im(

FCD

)

f

=

h

(

FCD

)

f

i

1

F

(Src

f

)

=

Dst

f

h

F

i

(Src

f

)

|

F

up

f

 

=

Dst

f

im

F

|

F

up

f

 

=

Dst

f

h

im

i

up

f

= im

f

.

dom(

FCD

)

f

= dom

f

is similar.

Proposition 35

(

FCD

)(

f

(

RLD

B

)) = (

FCD

)

f

(

FCD

B

)

for every reloid

f

and

A ∈

F

(Src

f

)

and

B ∈

F

(Dst

f

)

.

Proof

(

FCD

)(

f

(

RLD

B

)) = (

FCD

)(

I

RLD

B

f

I

RLD

A

) = (

FCD

)

I

RLD

B

(

FCD

)

f

(

FCD

)

I

RLD

A

=

I

FCD

B

(

FCD

)

f

I

FCD

A

= (

FCD

)

f

(

A ×

FCD

B

).

Corollary 16

(

FCD

)(

f

|

A

) = ((

FCD

)

f

)

|

A

)

for every reloid

f

and f.o.

A

.

Proposition 36

h

(

FCD

)

f

i X

= im (

f

|

X

)

for every reloid

f

and f.o.

X

.

Proof

im (

f

|

X

) = im (

FCD

) (

f

|

X

) = im(((

FCD

)

f

)

|

X

) =

h

(

FCD

)

f

i X

.

55